2007
DOI: 10.1111/j.1479-828x.2007.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐risk human papillomavirus DNA testing and high‐grade cervical intraepithelial lesions

Abstract: HPV DNA testing is a useful indicator in the management of patients with ASC-US and plays an important role in the evaluation of risk for CIN 2,3 and cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The pooled absolute specificity for excluding CIN2 + and CIN3 + was 45% (95% CI, 41%‐50%) and 42% (95% CI, 34%‐51%), respectively (Table and Fig. ) . The corresponding SROC plots for the outcomes of CIN2 + and CIN3+, shown in Figure , display the variation of the test accuracy in the individual studies as well as the overall pooled accuracy.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…The pooled absolute specificity for excluding CIN2 + and CIN3 + was 45% (95% CI, 41%‐50%) and 42% (95% CI, 34%‐51%), respectively (Table and Fig. ) . The corresponding SROC plots for the outcomes of CIN2 + and CIN3+, shown in Figure , display the variation of the test accuracy in the individual studies as well as the overall pooled accuracy.…”
Section: Resultsmentioning
confidence: 95%
“…An overview of the study design, population, and test characteristics of the included studies is presented in Supporting Table 1 (see online supporting information). Eight reports had a prospective design, and 17 reports had a retrospective design . Eighteen studies included women with ASC‐H identified through primary screening, and 7 studies recruited subjects in colposcopy clinics to which women had been referred because of a prior cytological result of ASC‐H .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations